Cross‐linked casein micelle used as encapsulating agent for jaboticaba (Plinia jaboticaba) phenolic compounds by spray drying. (23rd March 2020) - Nogueira, Márcio H; Tavares, Guilherme M; Casanova, Federico; Silva, Carolina RJ; Rocha, Juliana CG; Stringheta, Paulo C; Stephani, Rodrigo; Perrone, Ítalo Tuler; de Carvalho, Antonio F
Abstract : Phenolic compounds from jaboticaba ( Plinia jaboticaba ) fruit were encapsulated by spray drying using transglutaminase cross‐linked casein micelles as encapsulating agents. The encapsulations were performed at pH 2.0 and pH 7.0. The addition of phenolic compounds did not dramatically alter the water activity or the morphology of the obtained powders. Despite some degradation of the phenolic compounds encapsulated with the cross‐linked casein micelles at pH 2.0 during the spray‐drying process, the compounds' antioxidant capacity remained stable after drying. The results clearly demonstrate the potential use of cross‐linked casein micelles as encapsulation agents at highly acidic conditions.